Identifikasi Dampak Lalu Lintas Terminal Tipe C Borobudur dan Area Parkir Spesifik di Kabupaten Magelang - Yulianyahya, Raafi Widyaputra (Jurnal Aplikasi Teknik Sipil, 2024)
The terminal function is still needed to help community mobility, improve the economy, and increase local tourism, especially in the Borobudur Tourism area. In order for the Magelang City transportation arrangement to be maintained effectively, it is necessary to have a Type C Passenger Transport Terminal in Magelang Regency. The construction of this terminal can generate traffic and increase the burden of traffic around it, resulting in traffic disruptions that reduce the level of road services. Therefore, this study aims to calculate and analyze the impact of development activities that are useful to minimize the impact of traffic by providing appropriate recommendations. The research method was used with the approach of the 1997 Indonesian Road Capacity Manual (MKJI, 1997), with outputs used for delays and saturation degrees, where the delay values and saturation degrees were used to see existing conditions and predictions for the next 5 years. The results of the prediction analysis for 2028 show a significant increase in the degree of saturation on Jalan Syailendra Raya by 9-13% and also Jalan Pramudyawardhani by 11-15% judging from the existing conditions for both roads. Likewise, the increase in the degree of saturation in the performance of intersections around the development reaches 30-70%, as seen from existing conditions.